Implementation Open Artificial Intelligence ChattGPT Integrated With Whatsapp Bot - Alia, Putri Ariatna; Prayogo, Johan Suryo; Kriswibowo, Rony; Setyadi, Agung Teguh (Universitas PGRI Semarang, 2024)
The rapid development of internet technology has led to changes in human habits interms of seeking information. Now humans have a tendency to use smartphones to find information, especially by using the WhatsApp application. According to data compiled by creative agency we are social in 2023. Whatsapp is in the top position of the most used application, reaching 92%. Artificial intelligence is used as a tool to create remote services to customers because there are no restrictions on working time and can only be accessed using a smartphone. GPT (Generative Pre-training Transformer) chat technology has the ability to answer questions, as well as understand the context of the conversation and generate meaningful text like a remote conversation with humans. ChattGPT can provide information to users with these capabilities, especially in terms of health. In the research there is an integration process between Chattgpt and Whattsapp, by entering the API (Application Programming Interface) key Chattgpt into Whattsapp with the help of javascript programming language. So that the artificial intelligence system using ChattGPT can be implemented on whattapp.